A New POD Method for Transport Equations - Solán Fustero, Pablo; Navas Montilla, Adrián; Gracia Lozano, José Luis; García Navarro, Pilar (Jornada de Jóvenes Investigadores del I3A, 2021)
A novel implementation of the reduced-order model (ROM) of 1D advection-diffusion equation by means of a modified Proper Orthogonal Decomposition (POD) method is presented. This modified method is based on a coordinate transformation (CT-POD) that allows prediction beyond a training time horizon for advection dominated equations.